Homogentisic acid-derived pigment as a biocompatible label for optoacoustic imaging of macrophages - Ina Weidenfeld (Nature Portfolio, 2019)
The ability to image macrophages in vivo would provide insights into homeostasis and disease but current imaging agents have effects on viability and functionality. Here the authors develop an optoacoustic probe based on a homogentisic acid-derived pigment related to melanin, capable of visualizing macrophage migration in mice.